2016
DOI: 10.1093/scan/nsw027
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in autism: a resting-state fMRI investigation of functional brain connectivity in males and females

Abstract: Autism spectrum disorders (ASD) are far more prevalent in males than in females. Little is known however about the differential neural expression of ASD in males and females. We used a resting-state fMRI-dataset comprising 42 males/ 42 females with ASD and 75 male/75 female typical-controls to examine whether autism-related alterations in intrinsic functional connectivity are similar or different in males and females, and particularly whether alterations reflect 'neural masculinization', as predicted by the Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
159
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(179 citation statements)
references
References 63 publications
16
159
3
1
Order By: Relevance
“…This might not only open new possibilities for experimental research but also lead to new therapeutic applications in diseases where resting-state connectivity is diminished as, for example, in autism or Alzheimer's disease (Greicius, 2008;Alaerts et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might not only open new possibilities for experimental research but also lead to new therapeutic applications in diseases where resting-state connectivity is diminished as, for example, in autism or Alzheimer's disease (Greicius, 2008;Alaerts et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This could open new opportunities for human fMRI research and new interventional approaches for modulating long-range connectivity of the human brain at rest. Potential therapeutic applications could be, for example, tACS-based modulation in patients with diminished resting-state connectivity within specific circuits, as for example in autism (Alaerts et al, 2014) and Alzheimer's disease (Greicius, 2008).…”
Section: Distribution Of the Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Moreover, gender has recently been shown to modulate the direction of connectivity differences in ASD. 8 In contrast, another study found default mode network (DMN) hypo-connectivity in both genders. 9 Finally, another source of bias that has been largely overlooked is the impact of age-related changes on functional connectivity.…”
Section: Introductionmentioning
confidence: 94%
“…By contrast, Di & Biswal12 found solely sex-independent, large-scale neuroanatomical alterations in children with ASD, which were deemed to be consistent with the predictions of EMB theory. On the other hand, Alaerts et al 13. identified highly-consistent patterns of functional hypo-connectivity in ASD males compared to TD males, and hyper-connectivity in females with ASD compared to TD females.…”
mentioning
confidence: 99%